2019
DOI: 10.3390/rs11020191
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Flood Progress Monitoring in Cropland with NASA SMAP

Abstract: Research in different agricultural sectors, including in crop loss estimation during flood and yield estimation, substantially rely on inundation information. Spaceborne remote sensing has widely been used in the mapping and monitoring of floods. However, the inability of optical remote sensing to cloud penetration and the scarcity of fine temporal resolution SAR data hinder the application of flood mapping in many cases. Soil Moisture Active Passive (SMAP) level 4 products, which are model-driven soil moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Due to the high level of cloud contamination during the monsoon time, cloud-free Landsat images identification was difficult for flood mapping [85]. For Bangladesh, one of the best opportunities for operational flood mapping comes from Sentinel-1 imaging as it is publically available [63]. In Bangladesh, the agriculture sector is greatly impacted by floods, despite conventional flood management systems paying very limited attention to this sector [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high level of cloud contamination during the monsoon time, cloud-free Landsat images identification was difficult for flood mapping [85]. For Bangladesh, one of the best opportunities for operational flood mapping comes from Sentinel-1 imaging as it is publically available [63]. In Bangladesh, the agriculture sector is greatly impacted by floods, despite conventional flood management systems paying very limited attention to this sector [63].…”
Section: Discussionmentioning
confidence: 99%
“…Box plots were used to show the statistical distribution of the data. A distinct separable backscatter value for water and other classes was used for image classification [44,63].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, crop loss assessment models based on the soil-water balance can benefit from the recent launch of NASA's Soil Moisture Active Passive (SMAP) mission. Rapid flood progress monitoring in cropland using soil saturation can be mapped using SMAP data [58,118].…”
Section: Discussionmentioning
confidence: 99%
“…Although no use of Sentinel-1 data was reported in these selected case studies, there is a high possibility of the use of Sentinel-1 in the near future because of the free-of-charge availability. Sentinel-1 provides C-band SAR data with multiple polarization, which is suitable for both flood mapping and crop condition monitoring [58].…”
Section: Remote Sensing Data Utilizationmentioning
confidence: 99%
“…Remote sensing offers a unique method to study the sea surface salinity (SSS) associated with various oceanic and climatological phenomena [28][29][30]. Launched in January 2015, NASA's Soil Moisture Active Passive (SMAP) platform and mission provide unique and complementary observations to study floods and discharged freshwater in coastal estuarine regions [31,32]. Using in situ salinity data, Tang et al [33] validated the SMAP SSS and suggested that the SMAP can track large salinity changes occurring within a month.…”
Section: Madden-julian Oscillation-related Offshore Transport Of the mentioning
confidence: 99%